Extent of Forensic Practices of Police Investigators: A Basis for Enhancement Plan - Quiape, Japhet; Painaga, Ermee Joy (JPAIR Multidisciplinary Research, 2023)
In criminal investigations, the Directorate for Investigation and Detective Management – Police investigators are required by Philippine National Police orders to conduct forensic science-based crime scene investigations. In order to ensure that every government employee adheres to the accepted belief that public office is a public trust, it is challenging to assess the work of police detectives performing crime scene investigations using forensic technology. This essential value of forensic science in police investigations is undeniable. This study discusses the scope of police forensic methods in ballistics, photography, and dactyloscopy, specifically in the Province of Antique. These issues regarding the scope of practices in conducting investigations and forensic examinations are expressed via a survey questionnaire and a series of statistical tests. In addition, the report outlines the difficulties experienced by these Philippine National Police investigators. The results of the study found that police investigators had a high level of forensic experience with ballistics and photography. Further, results revealed low level of forensic experience with dactyloscopy.. Therefore, Police investigators, among many solutions, may consider the following to be of great help: 1-attending relevant seminars and trainings involving dactyloscopy, and 2- specifying budget allocation for lacking equipment.